Cardiac glycoside-mediated turnover of Na, K-ATPases as a rational approach to reducing cell surface levels of the cellular prion protein - Mehrabian, Mohadeseh; Wang, Xinzhu; Eid, Shehab; Yan, Bei Qi; Grinberg, Mark; Siegner, Murdock; Sackmann, Christopher; Sulman, Muhammad; Zhao, Wenda; Williams, Declan; Schmitt-Ulms, Gerold (PloS one, 2022)
It is widely anticipated that a reduction of brain levels of the cellular prion protein (PrP C ) can prolong survival in a group of neurodegenerative diseases known as prion diseases. To date, efforts to decrease steady-state PrP C levels by targeting this protein directly with small molecule drug-like compounds have largely been unsuccessful. Recently, we reported Na,K-ATPases to reside in immediate proximity to PrP C in the brain, unlocking an opportunity for an indirect PrP C targeting approach that capitalizes on the availability of potent cardiac glycosides (CGs). Here, we report that exposure of human co-cultures of neurons and astrocytes to non-toxic nanomolar levels of CGs causes profound reductions in PrP C levels. The mechanism of action underpinning this outcome relies primarily on a subset of CGs engaging the ATP1A1 isoform, one of three α subunits of Na,K-ATPases expressed in brain cells. Upon CG docking to ATP1A1, the ligand receptor complex, and PrP C along with it, is internalized by the cell. Subsequently, PrP C is channeled to the lysosomal compartment where it is digested in a manner that can be rescued by silencing the cysteine protease cathepsin B. These data signify that the repurposing of CGs may be beneficial for the treatment of prion disorders.